Competence: Canon 1673 (Roman replies and CLSA advisory opinions 1996, 1996)
Entries dealing with questions of competence are found in both the 1994 and 1995 editions of Roman Replies. This year also includes additional correspondence concerning canon 1673, §3, between a diocese in the United States (whose “request for competence” was apparently somewhat different from the standard form) and the Apostolic Signatura. The reply of the Signatura is in English.